Interfacial and emulsifying properties of mealworm protein at the oil/water interface - Gould, Joanne; Wolf, Bettina (Elsevier, 2017)
The increasing global population and consumer demand for protein will render the provision of protein a serious future challenge. The lower environmental impact of insect farming makes the consumption of insects an appealing solution, although consumers in developed countries often respond to the idea of eating insects with disgust. One approach to accustom consumers to insects as part of their diet is through the application of functional insect extracts as food ingredients. Here, the interfacial and emulsion properties of protein extracted from Tenebrio molitor (MP) was investigated in comparison to commercial whey protein (WP). The MP showed higher interfacial activity and faster adsorption kinetics at the oil/water interface. The mean droplet size of high shear processed oil-in-water (o/w) emulsions (20% w/w oil) stabilised with MP assumed a process limited value at the lowest protein concentration, included in this study, of 0.44% w/w based on aqueous phase. Stepwise increase in protein concentration to 0.88%, 1.75% and 2.63% revealed, in the case of WP stabilised emulsions, that the same process limited droplet diameter was reached at 1.75% protein addition. With a view to potential future application of MP as a food emulsifier MP stabilised emulsions were exposed to common formulation and process conditions such as varied pH, salt, heat, chilling and freezing. Except for flocculation after heating to 90 °C and at pH close to the isoelectric point (IEP) of the MP, the microstructure of the emulsions remained unchanged. MP shows promise as a food emulsifier and represents a vehicle for the introduction of insect protein into the diet of societies not accustomed to eating insects.